2019
DOI: 10.1113/ep087531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antiarrhythmics on the electrical restitution in perfused guinea‐pig heart are critically determined by the applied cardiac pacing protocol

Abstract: New Findings What is the central question of this study?Are modifications in the restitution of ventricular action potential duration induced by antiarrhythmic drugs the same when assessed with premature extrastimulus application at variable coupling intervals (the standard stimulation protocol) and with steady state pacing at variable rates (the dynamic stimulation protocol)? What is the main finding and its importance?With class I and class III antiarrhythmics, the effects on electrical restitution determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Electrical restitution curves describing the relationship between ARI and prior diastolic interval were formulated. The maximum slope of the electrical restitution curve is a measure of myocardial arrhythmogenic potential, with greater slopes indicating a higher risk of ventricular arrhythmogenicity (Taggart et al, 2003;Osadchii, 2012Osadchii, , 2019. ARI and diastolic interval were measured, and electrical restitution curves were composed, and the maximum steep slope (S max ) was calculated using a logarithmic approximation approach (Howard-Quijano et al, 2017b).…”
Section: (B) Programmed Ventricular Extrastimulation (S1/s2 Pacing) and Electrical Restitutionmentioning
confidence: 99%
“…Electrical restitution curves describing the relationship between ARI and prior diastolic interval were formulated. The maximum slope of the electrical restitution curve is a measure of myocardial arrhythmogenic potential, with greater slopes indicating a higher risk of ventricular arrhythmogenicity (Taggart et al, 2003;Osadchii, 2012Osadchii, , 2019. ARI and diastolic interval were measured, and electrical restitution curves were composed, and the maximum steep slope (S max ) was calculated using a logarithmic approximation approach (Howard-Quijano et al, 2017b).…”
Section: (B) Programmed Ventricular Extrastimulation (S1/s2 Pacing) and Electrical Restitutionmentioning
confidence: 99%
“…It has been known for a long time that the APD/ERP of an extrasystole depends on the proximity of the preceding beat, called diastolic interval; and as the diastolic intervals increase, the APDs/ERPs of the extra beats also increase. This process is called electrical restitution and had been described long ago (Nolasco and Dahlen, 1968;Boyett and Jewell, 1978;Elharrar and Surawicz, 1983), but its importance in arrhythmia research gained particular attention again in the past two decades (Gilmour, 2002;Franz, 2003;Kalb et al, 2004;Gilmour, 2009;Orini et al, 2016;Osadchii, 2017a;Osadchii, 2017b;Shattock et al, 2017;Orini et al, 2019;Osadchii, 2019). According to the restitution hypothesis, as diastolic intervals increase due to propagation of an extrasystole, the next following possible extrasystole would encounter prolonged APD/ERP and local conduction defect can occur.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in different preparations investigated the effects of antiarrhythmic drugs on the cardiac electric restitution properties (Varróet al, 1985;Hsieh et al, 2013;Osadchii, 2017a;Osadchii, 2017b;Shattock et al, 2017). These studies yielded different results depending on the protocols (dynamic or standard), on the basic stimulation frequencies, on the preparations (ventricular muscle or Purkinje fibers), and on the species (guinea-pig, rabbit, rat, or dog) used in their experimental approaches (Elharrar and Surawicz, 1983;Kalb et al, 2004;Orini et al, 2016;Shattock et al, 2017;Osadchii, 2019). The species used may have special significance, since, as Figure 2 shows, there are marked differences between restitution curves measured in ventricular papillary muscle from different species (in rat, guinea-pig, rabbit, dog or human preparations) with the same experimental restitution pacing protocol and basic stimulation frequency.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in the Supplementary Material 3, it can be obtained by using a standard stimulation (S1S2) protocol (an extra stimulus application at different coupling intervals after a series of regular pacing pulses) or by using a dynamic pacing protocol (S1S1; steady pacing at gradually increasing rates). While both protocols have been used to measure APD restitution, the restitution curve in standard stimulations is a measure of the immediate response to basic cycle length (BCL) changes, whereas the dynamic restitution curve is a measure of the steady-state response (Jing et al, 2015;Osadchii, 2019). Previous studies have indicated that steady-state alternans may be better described by APD adaptation dynamics, depending on both the steady-state relationship between the BCL and APD and the restitution curve (Osadchii, 2019).…”
Section: General Description Of the Apd Restitution Theorymentioning
confidence: 99%
“…While both protocols have been used to measure APD restitution, the restitution curve in standard stimulations is a measure of the immediate response to basic cycle length (BCL) changes, whereas the dynamic restitution curve is a measure of the steady-state response (Jing et al, 2015;Osadchii, 2019). Previous studies have indicated that steady-state alternans may be better described by APD adaptation dynamics, depending on both the steady-state relationship between the BCL and APD and the restitution curve (Osadchii, 2019). The stability of AP alternans can be shown by the cobweb plots (Figure 3).…”
Section: General Description Of the Apd Restitution Theorymentioning
confidence: 99%